Systematic Review : Kekerasan Seksual Terhadap Anak : Bagaimana Peran Ahli Forensik? - agustina, riskia (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 2 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i02.p06, 2022)
Cases of immoral crimes such as sexual violence never show an end. It is not only adults who are the targets of the perpetrators, but also children who are the targets of their crimes. There is no longer a safe and comfortable zone, be it a social environment or even a school. Perpetrators of sexual violence are not only strangers, even relatives to their own family can be the mastermind behind their crimes. This writing has the aim of knowing how urgency an act of proof is in a criminal case. Article 184 paragraph (1) of the Criminal Procedure Code states that valid evidence consists of: witness statements, expert statements, letters, instructions and statements of the defendant. The important role of an expert in providing information and proving criminal cases relating to the body and soul are regulated in the criminal procedural law evidentiary system. So that it can produce conclusions and penalties that are relevant to the type of crime committed, both in the form of prison sentences and fines.